Hey guys/gals i am doing this equation and am stuck at this point (bx) - ((ap-a^2x)/b) i don't even know where to start thanks Josh
Follow Math Help Forum on Facebook and Google+
Originally Posted by sinners Hey guys/gals i am doing this equation and am stuck at this point (bx) - ((ap-a^2x)/b) i don't even know where to start thanks Josh Did u mean this .. $\displaystyle bx-\frac{ap-a^2x}{b}$ What are you trying to find ? Simplify ?
yes soz i forgot the last part all of that equals q, solve for x thanks Josh
$\displaystyle bx-\frac{ap-a^2x}{b}=q$ $\displaystyle \frac{b^2x-ap+a^2x}{b}=q$ $\displaystyle b^2x+a^2x=bq+ap$ $\displaystyle (b^2+a^2)x=bq+ap$ $\displaystyle x=\frac{bq+ap}{b^2+a^2}$
View Tag Cloud